The influence of mobile health intervention on the rate of prenatal diagnosis and pregnancy outcomes among pregnant women with high-risk prenatal screening results: protocol for a randomized controlled trial - Wang, Jie; Wang, Jing; Jiang, Yang; Liu, Yaxian; Bao, Rantong; Wang, Hong; Huang, Yan; An, Jin; Wang, Xiaohua; Wang, Fei (Frontiers in Psychiatry, 2025)
BackgroundPrenatal diagnostics is a crucial process for ensuring the health of both pregnant women and their fetuses. However, the participation rate of high-risk pregnant women in prenatal diagnostics is often influenced by various factors, including anxiety, depression, and lack of family support. In recent years, mobile health (mHealth) interventions have become an important tool in improving maternal health management, especially in terms of behavior change. The Behavior Change Wheel (BCW) theory and the Family Health Theory (FHT) have been applied in various health interventions, but there are limited studies focusing on prenatal diagnostics.ObjectiveThe study aims to evaluate the impact of a mobile health intervention based on the Behavior Change Wheel theory and Family Health Theory on prenatal diagnostic participation rates and pregnancy outcomes in high-risk pregnant women, while exploring the role of family member involvement in improving maternal psychological health and pregnancy outcomes.MethodsThe study outlines a single-blind, interventional, randomized controlled trial conducted at the Inner Mongolia Maternity and Child Health Care Hospital. A total of 58 high-risk pregnant women will be included and randomly assigned to either the intervention group (29 participants) or the standard care group (29 participants). The intervention group will receive a 12-week mHealth intervention via the WeChat platform, including health education, emotional support, behavioral feedback, and family member participation. The standard care group will receive standard prenatal care. Primary outcomes include prenatal diagnostic needs and pregnancy outcomes, while secondary outcomes include health knowledge, anxiety and depression levels, decision conflict, and other factors. This study uses IBM SPSS Statistics 24.0 for data analysis, employing descriptive statistics, normality tests, Mann–Whitney U, Wilcoxon, and chi-square tests.DiscussionThe study proposes that a mobile health intervention based on the Behavior Change Wheel theory and Family Health Theory may effectively increase prenatal diagnostic participation and improve the psychological health and pregnancy outcomes of high-risk pregnant women. The active participation and emotional support of family members are expected to be key components in achieving these improvements. This research provides new insights and evidence for the application of mHealth interventions in prenatal screening.